Renocardiovascular Biomarkers: from the Perspective of Managing Chronic Kidney Disease and Cardiovascular Disease - Niizuma, Shinichiro; Iwanaga, Yoshitaka; Yahata, Takaharu; Miyazaki, Shunichi (Frontiers in Cardiovascular Medicine, 2017)
Mortality among the patients with chronic kidney disease (CKD) and end-stage renal disease (ESRD) remains high because of the very high incidence of cardiovascular disease (CVD) such as coronary artery disease, cardiac hypertrophy, and heart failure. Identifying CVD in patients with CKD/ESRD remains a significant hurdle and the early diagnosis and therapy for CVD is crucial in these patients. Therefore, it is necessary for the better management to identify and utilize cardiovascular (CV) biomarkers in profiling CVD risk and enabling stratification of early mortality. This review summarizes current evidence about renocardiovascular biomarkers; CV biomarkers in patients with CKD as well as with ESRD, emphasizing on the emerging biomarkers: BNPs, cardiac troponins, copeptin, the biomarker of renal injury (NGAL), and mineral and bone disorder hormones/marker (FGF-23). Furthermore, it discusses their potential roles especially in ESRD and in future diagnostic and therapeutic strategies for CVD in the context of cardiorenal syndrome.